PERAN LINGKUNGAN SEKOLAH DALAM MEMBENTUK KEMANDIRIAN DAN AKHLAK TERPUJI ANAK USIA DINI DI TKIT PERMATA HATI: THE ROLE OF THE SCHOOL ENVIRONMENT IN DEVELOPING INDEPENDENCE AND EXEMPLARY CHARACTER IN EARLY CHILDHOOD AT TKIT PERMATA HATI - Fatimah Asroriah; Jenny Bintang Pramesty (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
This study aims to investigate the influence of the school environment on the development of independence and the inculcation of commendable moral values in early childhood. The research was conducted using a case study approach at TKIT Permata Hati. Early childhood education plays a fundamental role in laying the foundation for optimal and holistic individual development, encompassing cognitive, affective, and psychomotor aspects. During this period, the introduction to Islamic morals is built through habituation, exemplary modeling, and reinforcement from the immediate environment. The findings reveal that the school environment plays a significant role as an educational ecosystem that supports the growth of independence and noble morals through structured activity design. A key finding of the study emphasizes the importance of synergy between teachers and parents in providing consistent role modeling. The continuity of positive habituation activities both at school and at home, along with the utilization of Islamic stories and play activities imbued with moral values, proves effective in strengthening children's understanding and internalization of values. The study concludes that optimizing the role of the school environment, supported by strong collaboration with the family, is a crucial strategy for building the foundation of an independent and morally commendable character from an early age.